Validity and reliability of melasma quality of life scale questionnaire in Bahasa Indonesia for female patients - Aditya, Rubby; Hoemardani, Aida S. D.; Bernadette, Irma; Chandra, Levina; Balkrisnan, Rajesh (UI Scholars Hub, 2020)
Background: At present, there is no questionnaire in Bahasa Indonesia to assess the quality of life of female patients with melasma. The aim of this study is to adapt the existing English questionnaire, MELASQOL, into Bahasa Indonesia, and to assess its validity and reliability. Methods: This is a cross-sectional study consisting of two stages. The initial stage is cross-cultural and language adaptation. The final stage is the validity and reliability test. The original MELASQOL questionnaire is in English and is adapted into Bahasa Indonesia according to the cross-cultural and language adaptation guidelines. The subjects were recruited from two sites, The Cipto Mangunkusumo Hospital and a factory in Tangerang. A construct validity method was used for the validity analysis. Cronbach’s α was used for internal reliability analysis. Results: The initial stage involved 30 subjects, and 32 subjects were involved with the final stage. The validity of The MELASQOL Bahasa Indonesia was calculated by the item-total score. The correlation coefficient is 0.712–0.935. Its reliability was calculated by the Cronbach α score is 0.962. Conclusions: MELASQOL Bahasa Indonesia is a valid and reliable instrument for assessing the quality of life of female patients with melasma in Indonesia.